INVESTIGATION OF AERO-ACOUSTIC EFFICIENCY OF THE FAN PROFILE OF THE TURBOJET ENGINE WITH THE USING ANSYS - М. И. Кисляк; М. М. Митрахович (Авіаційно-космічна техніка та технологія, 2017)
The modification of aircraft engines is a complex process and such directions as investigation of the efficiency of the profile of the fan blade from the point of view of aero-acoustic characteristics require a special approach to the problem. One such approach is the use of a software environment that will allow to determine the most effective profile with minimal costs. This technique significantly speeds up the designer and research department, allowing for a minimum period of preliminary investigation of the parameters of the fan and take all the necessary measures.